KUALITAS PELAYANAN KUNJUNGAN NEONATAL DENGAN TINGKAT KEPUASAN PASIEN DI PUSKESMAS DOLOK MERAWAN KABUPATEN SERDANG BEDAGAI - Sunengsih, Sunengsih; Aritonang, Barita; Ginting, Desideria Yosepha (NHM PRESS, 2023)
One of the efforts to reduce the risk of infant mortality (IMR) such as premature birth, sepsis and pneumonia, shortness of breath and trauma and LBW is the visit of newborns (neonatal). Newborn visits are one of the intervention options to reduce newborn mortality and comprehensively measure the capacity of care to provide healthy newborn delivery services for mothers and children. The reduction in infant mortality must be accompanied by a high coverage of newborn visits. Reducing infant mortality is currently not up to par, so the quality of newborn care visits should be investigated more closely. The purpose of this study was to determine the quality of neonatal visit services at the Dolok Merawan Health Center, Serdang Bedagai Regency in terms of aspects of physical appearance (tangible), reliability (reliability), ability to understand (emphaty), responsiveness (responsiveness), and assurance of certainty (assurance). This research is a qualitative research with a phenomenological approach. Data collection was carried out in the form of observations, interviews, and focus group discussions (FGD) using the analytical technique. The results of the research conducted provide a statement that the quality of neonatal visit services has not run optimally. Of the five dimensions of service quality, there are four (4) service dimensions that are not optimal in supporting patient satisfaction. These four things are the midwife did not prepare a complete examination and only weighed, measured the temperature and recorded it in the visit book; midwives do not always make complete neonatal visits, lack of time for neonatal visit services, midwives rush to explain their illness, cramped neonatal visit service rooms where examination rooms are not separated from one another, and inadequate waiting rooms. Suggestions for institutions related to chair facilities in the waiting room are added to review and collect data on tools and facilities at the Puskesmas to procure or add and improve professionalism in carrying out neonatal visits.